Agricultural sustainability in the European Union: a review of concepts, policies and economic perspectives - Prigoreanu, Ioan; Grigore-Sava, Andreea; Avarvarei, Simona Catrinel; Radu, Gabriela; Păduraru, Ştefana-Beatrice; Gherasim, Roxana Elena; Chihulcă, Monica; Ignat, Gabriela (Frontiers in Agronomy, 2025)
IntroductionSustainability in European Union (EU) agriculture has become a priority in both academic research and public policy, reflecting its central role in shaping resilient and balanced development models. The European agricultural landscape is characterized by significant agronomic diversity, including cereals, oilseeds, protein crops, industrial crops, vegetables, fruits, and fodder crops that support the livestock sector. These are integrated into multiple production systems: conservation agriculture, organic farming, integrated crop management, permanent pastures, and agroforestry, each contributing differently to environmental protection, economic efficiency, and social equity. Land use structures reveal a mosaic of arable land, permanent pastures, permanent crops, and mixed systems, reflecting the climatic and socio-economic diversity of Europe. In this context, the study examines how the economic, social, and environmental dimensions of sustainability are conceptualized and integrated into EU agricultural strategies.MethodsThe study uses a multi-level methodological approach, integrating conceptual, legislative, empirical, and bibliometric analyses. First, key concepts of agricultural sustainability were examined through a systematic review of academic literature and EU policy documents. Second, a legislative analysis assessed the regulatory framework shaping sustainability, with a focus on the common agricultural policy and related instruments. Third, empirical evidence from recent studies on the economic and financial performance of EU farms was synthesized to identify the structural determinants of viability. Finally, a bibliometric assessment mapped publication dynamics and emerging research themes, allowing for the triangulation of results across methodological dimensions.ResultsThe findings indicate a significant intensification of academic and political interest in sustainable agriculture after 2016, driven mainly by climate change pressures, digital transformation, and structural changes in rural areas. Research trends highlight an increasing focus on eco-efficiency, digitalization, and performance-based sustainability indicators. Although the CAP remains the central policy instrument supporting the transition to sustainable agriculture, its effects are mixed: it provides income stability and supports environmental commitments, but also contributes to persistent disparities between countries and farm types. Empirical studies show that the economic viability of EU agriculture is strongly influenced by the financial management of farms, their capacity for innovation, and the degree to which policies are tailored to national and regional specificities.DiscussionThe literature and policy evidence converge on the conclusion that the sustainability of EU agriculture cannot be based on one-size-fits-all solutions. Instead, it requires flexible, integrated, and context-sensitive approaches that are aligned with the heterogeneity of European agricultural systems. The social dimension, in particular the involvement of farmers, generational renewal, and the resilience of rural communities, is emerging as an essential pillar of the green transition, alongside technological innovation and digitalization. The study emphasizes that achieving long-term sustainability in EU agriculture depends on balancing productivity with environmental restoration and ensuring equitable socio-economic opportunities across all Member States.